The Biochemical Basis of Hydroxymethylglutaryl-CoA Reductase Inhibitors as Neuroprotective Agents in Aneurysmal Subarachnoid Hemorrhage - George Kwok Chu Wong; Wai Sang Poon (MDPI AG, 2010)
Aneurysmal subarachnoid hemorrhage (SAH) has the highest morbidity and mortality rates of all types of stroke. Many aneurysmal SAH patients continue to suffer from significant neurological morbidity and mortality directly related to delayed cerebral ischemia. Pilot clinical studies of the use of Hydroxymethylglutaryl-CoA Reductase Inhibitors (statins) in aneurysmal SAH patients have reported a reduction in delayed cerebral ischemia and better clinical outcomes. We review the biochemical effects of statins on endothelium vascular function, glutamate-mediated neurotoxicity, inflammatory changes, and oxidative injuries, with reference to their possible neuroprotective effects in aneurysmal SAH.